Research progress on the treatment of hair loss diseases with microneedle - LV Juan; ZHOU Jing (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
In recent years, both domestic and international studies have demonstrated therapeutic benefits of microneedles with various depth in the treatment of androgenetic alopecia, alopecia areata, and telogen effluvium. The mechanisms of microneedle therapy for alopecia may be related to the enhancement of transdermal drug delivery. In addition, various growth factors generated during microneedling participate in multiple hair loss-related signaling pathways, thereby promoting the formation of hair follicles during the growth phase. This article introduces microneedle treatments for different types of hair loss diseases and the selection of microneedle depth, aiming to provide reference for clinical treatment.